PELATIHAN MERANCANG DAN MEMASARKAN BRAND - Dorina Widowati; Wiwik Robiatul Adawiyah; Willy Arafah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, particularly in creating equal economic opportunities, alleviating poverty, and generating foreign exchange. However, many MSMEs still face challenges in marketing, especially in developing effective branding. The Azalea MSME Group, consisting mostly of housewives engaged in food businesses, operates traditionally without sufficient knowledge of marketing management. This community service program aimed to equip the Azalea MSME Group with knowledge and practical skills in creating and marketing brands. The method used was participatory training through counseling, practice in designing logos and packaging, and strategies for digital marketing using social media and marketplaces. The results showed that participants gained better understanding of marketing management, were able to design simple brand identities, and became more confident in promoting their products. This training contributes to strengthening the competitiveness and sustainability of MSMEs in the digital era